3D aeromagnetic imaging of Iwate volcano, northeast Japan. Issue 1 (1st December 2016) - Okuma, Shigeo; Nakatsuka, Tadashi; Kageura, Ryota
Abstract : Iwate volcano, northeast Japan is an active Quaternary volcano and is comprised of two parts: West-Iwate and East-Iwate. These bodies are underlain by early-middle Pleistocene volcanic rocks. In 1999, fumarolic areas were newly emerged along the ridge between Ubakura and Kurokura Mountains in West-Iwate and Iwate volcano was thought that an eruption was impending in 2000. However, the fumarolic activity has decreased since its peak in July 2001, and the disaster seems to have passed. In late 2000, a helicopter-borne EM and magnetic survey was conducted over Iwate volcano to better understand the subsurface structure of the volcano related to the ongoing volcanic activity. Recently we have conducted three-dimensional (3D) imaging of Iwate volcano to constrain its subsurface structure. Our model indicates that magnetization highs occupy the main edifice of East-Iwate, which reflects the surface and/or subsurface distribution of basaltic lavas. Meanwhile, magnetization lows are dominant inside the summit caldera of West-Iwate except for a magnetic high over the Onashiro lava flow. Magnetization highs are also distributed on the northern and southern slopes of West-Iwate but local magnetization lows lie on the heads of narrow valleys, corresponding to hydrothermal altered areas. These hydrothermal altered areas are also characterized by resistivity lows observed by the Airborne EM survey. Although the imaging improved our understanding of the surface and subsurface distribution of volcanic rocks in Iwate volcano, some limitations exist. No information about the magmas which should have intruded during the recent eruptive crisis was obtained by the imaging. The small magnetic contrast between the intruded magmas and their host rocks is the most probable reason.